Development of Android Application for Ordering Vegetables and Food Condiments - Brata, Adam Hendra; Brata, Komang Candra; Mahendra, Arya Yudha (Edu Komputika Journal, 2024)
The growth of internet users continues to increase rapidly each year, supported by the growth of accompanying devices. Mobile applications are the main drivers of the increasing number of internet users. In Indonesia, internet users have reached 47% of the total population. Based on this data, around 46% use it to visit online trading sites. The phenomenon of the rise of online buying and selling is certainly very beneficial, especially for the residents of Malang City, where 34% of its population are traders. Supporting applications for conducting trade are essential for both merchants and consumers to facilitate the business process of buying and selling. This research will study the development of a buying and selling application between sellers and consumers, emphasizing ease of use. The development of this application uses the Mobile-D development model as a reference. The Mobile-D method was adopted because offers a development process well-suited for users who are not directly alongside the developers. Additionally, Mobile-D’s iterative nature allows it to accommodate changing requirements, making it ideal for gathering needs directly from the application’s end users. Based on the results of the study, user evaluations of the application showed a score more than 70, leading to the conclusion that the developed application is user-friendly and acceptable to users.